PERKEMBANGAN SISTEM HUKUM DI INDONESIA - Gokma Toni Parlindungan S (Ensiklopedia Education Review, 2022)
In England, law formation is traditional. namely through jurisprudence, because it is too slow and does not keep up with the changes in this modern era, it must quickly be assisted by the formation of law by law, so that law can meet the needs of modern society. Thus, in England the law does not only mean the judge's decision, but the judge's decision is added to the law, added to government (executive) policies based on applicable law, also added to habits that are recognized as good by the court, as well as by other state agencies. So that in Continental Europe the applicable arrangements are laws formed by the legislature. Meanwhile, the laws that are formed are more likely to be close to the interests of the legislature, and it is not uncommon for laws to always be left behind by the community because of the increasingly rapid development of society and times. Jurisprudence is only useful if there is a recht vacuum, where there are no laws or unclear arrangements, the judge is obliged to interpret the law. Islamic law in Indonesia is closer to Common Law than Civil Law, this is because Islamic law originates from God which is inscribed on its adherents, different from rules or laws formed by the legislature which apply to all people in a country.Keywords: Development, Legal System, Indonesia.